Experimenting for Sustainable Transport - Hoogma, Remco (Transport, Development and Sustainability Series, 2002)
Technological change is a central feature of modern societies and a powerful source for social change. There is an urgent task to direct these new technologies towards sustainability, but society lacks perspectives, instruments and policies to accomplish this. There is no blueprint for a sustainable future, and it is necessary to experiment with alternative paths that seem promising. Various new transport technologies promise to bring sustainability benefits. But as this book shows, important lessons are often overlooked because the experiments are not designed to challenge the basic assumptions about established patterns of transport choices. Learning how to organise the process of innovation implementation is essential if the maximum impact is to be achieved - it is here that strategic niche management offers new perspectives. The book uses a series of eight recent experiments with electric vehicles, carsharing schemes, bicycle pools and fleet management to illustrate the means by which technological change must be closely linked to social change if successful implementation is to take place. The basic divide between proponents of technological fixes and those in favour of behavioural change needs to be bridged, perhaps indicating a third way.